KINERJA PEGAWAI NEGERI SIPIL DALAM PELAYANAN PUBLIK SAAT PANDEMI COVID-19 DI KANTOR KECAMATAN TIKALA KOTA MANADO - Daddy Markus Nalle; Maria H. Pratiknjo; Grace J. Walele (AGRI-SOSIOEKONOMI, 2021)
This study aims to find out and examine in depth about the performance of civil servants in public services at the Tikala Sub-District Office during the Covid-19 pandemic. The method used in this research is descriptive qualitative research method. Sources of data used in this study are divided into two types, namely primary data and secondary data. The steps used in data analysis techniques are editing, data classification, then drawing conclusions. The results showed that the performance of civil servants at the Tikala sub-district office was not as expected, because the service during the pandemic was not the same as before the Covid-19 pandemic. Working from home during the Covid-19 pandemic did not go as expected, because the service activities at the Tikala District office were work that had to be completed at the office, not at home.